Transportan 10 improves the pharmacokinetics and pharmacodynamics of vancomycin - Ruczyński, Jarosław (Sci Rep, 2019)
In the presented study, transportan 10 (TP10), an amphipathic cell penetrating peptide (CPP) with high translocation activity, was conjugated with vancomycin (Van), which is known for poor access to the intracellular bacteria and the brain. The antibacterial activity of the conjugates was tested on selected clinical strains of methicillin-resistant Staphylococcus aureus (MRSA) and Enterococcus sp. It turned out that all of them had superior antimicrobial activity in comparison to that of free Van, which became visible particularly against clinical MRSA strains. Furthermore, one of the conjugates was tested against MRSA - infected human cells. With respect to them, this compound showed high bactericidal activity. Next, the same conjugate was screened for its capacity to cross the blood brain barrier (BBB). Therefore, qualitative and quantitative analyses of the conjugate’s presence in the mouse brain slices were carried out after its iv administration. They indicated the conjugate’s presence in the brain in amount >200 times bigger than that of Van. The conjugates were safe with respect to erythrocyte toxicity (erythrocyte lysis assay). Van in the form of a conjugate with TP10 acquires superior pharmacodynamic and pharmacokinetic.